Characterization of Propane Fueled Flames: A Significant Source of Brown Carbon - Jai Prakash; Kalyan Mitra; Harsh Raj Mishra; Xiangyu Pei; Evert Ljungström; Ravi Kant Pathak (Atmosphere, 2022)
In this study, we developed a framework for interpreting the in situ morphological properties of black carbon (BC, also referred to as “soot” due to combustion relevance) mixed with primary organic aerosol. Integration of the experiment considering primary organic aerosol (POA) evaporation from the soot particles was examined using a Differential mass–mobility analyzer (DMA) and showed the untold story of the mixing of BC and POA. We also hypothesize that morphological transformation of soots and determined such as (i) the evaporation of externally and internally mixed POA led to a decline in the particle number and size of monodisperse aerosol; (ii) presence of externally mixed BC was interpreted from the occurrence of two peaks of soot upon heating; (iii) heat-induced collapse of the BC core possibly resulted from the evaporation of material from the voids and effect of heat; (iv) volume equivalent to changes in the mobility diameter represented evaporation of POA from the surface and collapse upon heating. POA constituted a high fraction (20–40% by mass) of aerosol mass from these flames and was predominantly (i.e., 92–97% by mass) internally mixed with BC. POA was found to be highly light absorptive, i.e., an Ångström absorption exponent (AAE) value of (in general) >1.5 was estimated for BC + POA at 405/781 nm wavelengths. Interestingly, a much more highly absorptive POA [mass absorption cross-section (MAC)-5 m2 g−1] at 405 nm was discovered under a specific flame setting, which was comparable to MACs of BC particles (8–9 m2 g−1).